2020
DOI: 10.21203/rs.3.rs-76115/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HIV Prevention at Drug Shops: Awareness and Attitudes Among Shop Dispensers and Young Women About Oral Pre-Exposure Prophylaxis and The Dapivirine Ring in Shinyanga, Tanzania

Abstract: Background: HIV risk remains high among adolescent girls and young women (AGYW, ages 15-24) in Tanzania. Many AGYW experience stigma and provider bias at health facilities, deterring their use of HIV prevention services. Privately-owned drug shops, ubiquitous in many communities, may be an effective and accessible channel to deliver HIV prevention products to AGYW, including oral pre-exposure prophylaxis (PrEP) and the dapivirine vaginal ring. Methods: In July-August 2019, we enrolled 26 drug shops in Shinyang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…For example, several studies indicated that clients who routinely accessed private pharmacies for sexual and reproductive health services, such as emergency contraception and sexual performance-enhancing drugs, frequently reported behaviours associated with the risk of HIV acquisition (e.g. multiple sexual partners) [43,45,58,59,66,70]. In the pilot study of the nurse-led PrEP delivery model in Kenya, HIV risk behaviours, such as engaging in transactional sex or sex with a partner of unknown HIV status, were significantly more prevalent among AGYW accessing sexual and reproductive health services at private pharmacies than at public family planning clinics [59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, several studies indicated that clients who routinely accessed private pharmacies for sexual and reproductive health services, such as emergency contraception and sexual performance-enhancing drugs, frequently reported behaviours associated with the risk of HIV acquisition (e.g. multiple sexual partners) [43,45,58,59,66,70]. In the pilot study of the nurse-led PrEP delivery model in Kenya, HIV risk behaviours, such as engaging in transactional sex or sex with a partner of unknown HIV status, were significantly more prevalent among AGYW accessing sexual and reproductive health services at private pharmacies than at public family planning clinics [59].…”
Section: Discussionmentioning
confidence: 99%
“…In the studies that measured acceptability outcomes, our review suggests that while pharmacy-delivered HIV services are perceived to be largely acceptable, this may be conditional on pharmacy providers' ability to maintain clients' privacy [46,57,63,65,66] and provide high-quality services [53,55,63,67]. As such, implementers should consider interventions that might increase the privacy of pharmacy-delivered HIV services, such as integrating self-screening tools for HIV risk [74,75], delivering antiretroviral drugs in discrete packaging [76,77] and counselling clients in a private setting [62].…”
Section: Discussionmentioning
confidence: 99%
“…Primary healthcare services, sexual and reproductive health services, and services for mother and children are important opportunities for discussing HIV risk and offering combined prevention, not only in sub-Saharan Africa, but also in other countries, for any women who may be at risk [22]. In our search, we identified 4 articles [23–26] focused solely on women, and another 3 articles included females with males [15,16,27]. HPTN 076 [23] was a Phase II study to evaluate if rilpivirine (RPV) LA was safe as a PrEP strategy.…”
Section: Long-acting For Pre-exposure Prophylaxismentioning
confidence: 99%
“…Exit interviews in pharmacies in Tanzania showed that 79% of married women have interest in using PrEP, with 43% willing to use a vaginal ring [26]. In South Africa, among youths, almost all the individuals, irrespective of gender, would prefer lasting (>6 m), injections or implants in the arm, but women would prefer injections over implants, and a health clinic (over a pharmacy) as a site for injection [15].…”
Section: Long-acting For Pre-exposure Prophylaxismentioning
confidence: 99%
“…Provision of the full 28-day course of PEP at a single clinical visit, with ongoing remote adherence counselling, can reduce transport and cost barriers to the client [13,14]. PEP availability needs to be expanded to locations outside the clinics, such as through communitybased retail drug shops [15]. Community outreach needs to empower clients to increase consumer demand and PEP delivery systems that meet their needs.…”
mentioning
confidence: 99%